Dr. Brad has gone mad! - Gutman, Dan.; Paillot, Jim (New York : Harper, 2009)
Ella Mentry School counselor Dr. Brad believes wisecracking A.J. may be a genius and subjects him to some very weird tests to find out for sure.
Keywords: Schools; Counselors; Psychological tests; Humorous stories